Ferrofluid flow due to a rotating disk in the presence of a non-uniform magnetic field - Bhandari, Anupam; Kumar, V. (Zielona Góra: Uniwersytet Zielonogórski)
The flow of a ferrofluid due to a rotating disk in the presence of a non-uniform magnetic field in the axial direction is studied through mathematical modeling of the problem. Contour and surface plots in the presence of 10 Kilo-ampere/meter, 100 kilo-ampere/meter magnetization force are presented here for radial, tangential and axial velocity profiles, and results are also drawn for the magnetic field intensity. These results are compared with the ordinary case where magnetization force is absent.
Keywords: magnetization force; ferrofluid; rotating disk; magnetic field